Art and Science in the Practice of Nursing - Locsin, Rozzano C. (Journal of Research in Nursing-Midwifery and Health Sciences, 2012)
Nursing is an art and a science. Issues derived from this statement stems from the definitions and descriptions of the terms “art” and “science.” Historical and contemporary contexts dictate their meanings influencing its value in the practice of nursing. Advancing the concept of art and science as a unified formula for understanding nursing and it practice is crucial to the appreciation of nursing practice as a valuable aspect in the attainment and maintenance of human health and well-being.